Training in psychiatry: making person-centred care a reality. (10th May 2019) - ,
Abstract : The RCPsych curriculum for core trainees is currently undergoing review and revision. The Person-Centred Training and Curriculum Scoping Group, which fed into the revision, reported in 2018. This paper shares key findings from the report and offers suggestions on implementing person-centred care in postgraduate psychiatric training and assessment. The scoping group recommended that training and the curriculum should be explicitly person-centred. Among its other recommendations was that skills relating to person-centred practice should be assessed, and the planning, development and delivery of local MRCPsych courses should be co-produced alongside people with lived experience of mental health conditions. Declaration of interest: All authors contributed to the development and writing of College Report CR215.